2021
DOI: 10.3390/md20010022
|View full text |Cite
|
Sign up to set email alerts
|

A 13CO2 Enrichment Experiment to Study the Synthesis Pathways of Polyunsaturated Fatty Acids of the Haptophyte Tisochrysis lutea

Abstract: The production of polyunsaturated fatty acids (PUFA) in Tisochrysis lutea was studied using the gradual incorporation of a 13C-enriched isotopic marker, 13CO2, for 24 h during the exponential growth of the algae. The 13C enrichment of eleven fatty acids was followed to understand the synthetic pathways the most likely to form the essential polyunsaturated fatty acids 20:5n-3 (EPA) and 22:6n-3 (DHA) in T. lutea. The fatty acids 16:0, 18:1n-9 + 18:3n-3, 18:2n-6, and 22:5n-6 were the most enriched in 13C. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…322 A stable isotope labelling study using 13 CO 2 has indicated that a polyketide pathway is involved in polyunsaturated fatty acid biosynthesis in Tisochrysis lutea, with remarkably fast production of the fatty acids meaning 13 C incorporation into early components of the pathway is undetectable. 323 The anaerobic transformation of domoic acid (Pseudonitzschia spp.) by a consortium of benthic microbes (Dalian, China) was proled, indicating the role other microorganisms could play in the fate and effects of this important biotoxin in marine environments.…”
Section: Reviewmentioning
confidence: 99%
“…322 A stable isotope labelling study using 13 CO 2 has indicated that a polyketide pathway is involved in polyunsaturated fatty acid biosynthesis in Tisochrysis lutea, with remarkably fast production of the fatty acids meaning 13 C incorporation into early components of the pathway is undetectable. 323 The anaerobic transformation of domoic acid (Pseudonitzschia spp.) by a consortium of benthic microbes (Dalian, China) was proled, indicating the role other microorganisms could play in the fate and effects of this important biotoxin in marine environments.…”
Section: Reviewmentioning
confidence: 99%
“…Nannochloropsis sp. [49,50], Tisochrysis lutea [51,52], and Chaetoceros muelleri [53], and Nitzchia sp. [54] are some other strains with a high concentration of PUFAs.…”
Section: Fatty Acidsmentioning
confidence: 99%